Inclusive Teaching With Digital Technology: Supporting Literacy Learning in Play-Based Kindergartens (LEARNing Landscapes, 2018)
Young children who are English Language Learners or have special learning needs can find it difficult to communicate in kindergarten classrooms. Open-ended tablet applications offer multi-modal tools for these children to communicate their ideas, engage with others, and demonstrate and develop their knowledge and skills. They position students as the producers and creators of the literacy content. Using pedagogical strategies such as effective routines, opportunities to collaborate and share with peers, and modelling, kindergarten educators can employ open-ended iPad apps to support the literacy and digital learning of children who are English Language Learners or who have special learning needs.
Keywords: special learning needs students; literacy; digital technology